PENGARUH CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) BERBANTUAN VIDEO ANIMASI TERHADAP KETERAMPILAN SPEAKING SISWA KELAS III SDN 101864 GUNUNG RINTIH - Rani Tasya Ginting; Albert Sirait; Robenhart Tamba; Halimatussakdiah; Laurensia Perangin Angin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was conducted with the aim of determining the effect of implementing the Content and Language Integrated Learning (CLIL) approach assisted by animation video on the speaking skills of third grade students at SDN 101864 Gunung Rintih. This study employed a quantitative approach with a pre-experimental design in the form of a One Group Pretest-Posttest Design. The population and sample consisted of all 23 third grade students at SDN 101864 Gunung Rintih, selected using total sampling. Data were collected through oral performance tests (speaking test) covering six assessment aspects: pronunciation, vocabulary, grammar, intonation, fluency, and content mastery. The instrument was validated through expert judgment. Data were analyzed using descriptive and inferential statistics, including the Shapiro-Wilk normality test and Paired Sample t-test using IBM SPSS Statistics version 31. The results showed an increase in the mean score from 62.83 in the pretest to 82.39 in the posttest, with an improvement of 19.56 points. The Paired Sample t-test showed a significance value (Sig. 2-tailed) < 0.001, less than α = 0.05, leading to the rejection of H₀ and acceptance of Hₐ. It is concluded that the CLIL approach assisted by animation video has a significant effect on the speaking skills of third grade students at SDN 101864 Gunung Rintih.